Pemberian Rebusan Air Jahe (Zingiber officinale) Madu (Genus Apis) Dengan Penurunan Nyeri Haid (Dismenorhea) Pada Siswi SMA Argopuro Panti Jember - Septian Windayanti; Tut Rayani Aksohini Wijayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Menstruation is a natural process involving the shedding of the endometrial lining, which is rich in blood vessels, due to the absence of egg fertilization. One common issue experienced by adolescent girls during menstruation is menstrual pain, or dysmenorrhea, which can disrupt daily activities and reduce quality of life. Management of this condition can be approached through pharmacological or non-pharmacological methods. While pharmacological treatment involves the use of analgesics, non-pharmacological interventions such as consuming ginger-honey decoction are considered safer and more natural alternatives for relieving menstrual pain. This study aims to examine the effectiveness of ginger-honey decoction in reducing the intensity of primary dysmenorrhea among adolescent girls. The research employed a quasi-experimental design using a one-group pretest-posttest approach, involving 30 respondents who experienced primary dysmenorrhea. The sampling technique used was total sampling, and the data were analyzed using the Wilcoxon Sign Rank Test. The results showed a significance value of p = 0.000, which is lower than α = 0.05. Based on these findings, it can be concluded that there is a significant effect of ginger-honey decoction consumption on reducing dysmenorrhea pain among female students at SMA Argopuro Panti Jember.